Word of Mouth and Online Reviews Are More Influential Than Social Media for Patients When Selecting a Sports Medicine Physician - Dylan N. Greif, M.D; Harsh A. Shah, M.D; Dylan Luxenburg, B.S; Blake H. Hodgens, B.S; Anabel L. Epstein, B.A; Lee D. Kaplan, M.D; Julianne Munoz, M.D; Michael Letter, Ph.D., P.A.-C; Michael G. Baraga, M.D (Elsevier, 2022)
Purpose: To (1) identify the percentage of patients seen in an orthopaedic sports medicine practice who use social media and (2) identify the role that social media has in physician selection as compared with other factors. Methods: After institutional review board approval was received, new patients aged 18 years or older who attended a single orthopaedic sports medicine office from February 2020 to May 2021 were identified for inclusion. Sociodemographic information was recorded, and each patient was asked to fill out a questionnaire that assessed social media usage and online resources used to choose and formulate opinions regarding the patient's provider. Results: Two hundred patients met the inclusion criteria and completed the questionnaire. Of these, 96.5% reported social media use. The most common online method of searching for and identifying a physician was Google (50.5%). Social media outlets such as Facebook, Instagram, or LinkedIn were only used 15.5% of the time to search for and select a physician. Older patients were more likely to use recommendations from friends and family in their consideration when selecting a physician. Conclusions: Despite almost all participants stating that they use social media, only 15.5% of patients reported that they used social media to search for and potentially select their physician. Our study suggests that although social media can be a helpful tool for patient education, other factors such as physician education and physician reputation through word-of-mouth referrals, online reviews, and online ratings seem to play a larger role in the patient's selection of his or her physician. Clinical Relevance: This information may be of value to orthopaedic surgeons looking for ways to build their patient base, online reputation, or other aspects of their practice on the Internet.